Prognostic Value and Therapeutic Perspectives of CXCR Members in the Glioma Microenvironment - He, Jiarong; Jiang, Zhongzhong; Lei, Jiawei; Zhou, Wen; Cui, Yan; Luo, Biao; Zhang, Mingming (Frontiers in Genetics, 2022)
Background: CXCR (CXC Chemokine Receptor) is a complex of the immune-associated protein involved in tumor activation, invasion, migration, and angiogenesis through various chemical signals in the tumor microenvironment (TME). However, significant prognostic characteristics of CXCR members and their impact on the occurrence and progression of glioma have not yet been fully elucidated. Methods: In this research, we used Oncomine, TCGA, GTEx, and CGGA databases to analyze the transcription and survival data of glioma patients. Afterward, the influence of CXCR members on the TME was explored using comprehensive bioinformatics analysis. Results: The mRNA expression levels of CXCR1/2/3/4/7 were significantly up-regulated in glioma than in normal samples, whereas the mRNA expression level of CXCR5 was decreased. We then summarized the genetic alteration landscape of CXCR and identified two molecular subtypes based on CXCR expression patterns in glioma. The characteristics of CXCRs were also investigated, including the clinicopathological parameters, TME cell infiltration, and prognosis of patients with glioma. After Lasso and multivariable Cox regression, a CR-Score for predicting overall survival (OS) was constructed and the predictive performance of the signature was validated. The high-risk group was a significantly poorer prognostic group than the low-risk group as judged by the CR-Score (TCGA cohort, p <0.001, CGGA cohort, p<0.001). Moreover, the CR-Score was significantly correlated to the tumor-immune infiltration and cancer stem cell (CSC) index. A risk scale-based nomogram incorporating clinical factors for individual risk estimation was established thereby. Conclusion: These findings may pave the way for enhancing our understanding of CXCR modification patterns and developing better immune therapeutic approaches for glioma.